Effect of Three Rootstocks on Grapevine (Vitis vinifera L.) cv. Negrette, Grown Hydroponically. II. Acidity of Musts and Wines - Garcia, M.; Ibrahim, H.; Gallego, P.; Puig, P.H. (South African Journal of Enology and Viticulture, 2017)
The cultivar was found to have high potassium content in leaves, musts and wines. To study the contribution of rootstock to this problem, Negrette was grafted onto 101-14 Mgt, 3309 C and SO 4 and grown in the same nutrient solution.  The Negrette/3309 combination produced wines with the highest total acidity and tartaric acid content. This graft combination seems to be the best suited to increase the acidity of the must and wine of Negrette.